Composition andband gap tailoring of crestalline (GaN)1-x(ZnO)x solid solution nanowires for enhanced photoelectrochemical performance; Inorganic Chemistry; Vol. 57, iss. 9 - Li Jing; Liu Baodan; Wu Aimin; Yang Bing; Yang Wenjin; Liu Fei; Zhang Xinglai; An V. V. Vladimir Vilorievich; Jiang Xin (2018, 2018)
Title screen